A dictionary of genetics - King, Robert C.; Stansfield, William D., 1930-; Mulligan, Pamela Khipple, 1953- (Oxford ; New York : Oxford University Press, 2006)
"The publication of this fully updated edition of A Dictionary of Genetics coincides with the hundredth anniversary of the introduction of the term genetics by William Bateson in 1906, following the pioneering work of Gregory Mendel. Since then, genetics has made tremendous advances in knowledge and technique, and now occupies a pivotal position in the life sciences for probing fundamental questions in cell biology, development, and evolution. Proliferation of new terms inevitably accompanies such extraordinary advancement. This new edition of the Dictionary addresses the needs of students, educators, and clinical geneticists for an authoritative and up-to-date reference work that not only defines the latest terms, but in most cases, also presents important ancillary encyclopedic information."--BOOK JACKET.
A Dictionary of Genetics -- Classification -- Domesticated Species -- Periodicals Cited in the Literature -- Multijournal Publishers.
Includes bibliographical references (pages 570-575).
Print version record.
eBooks on EBSCOhost
Keywords: Genetics -- Dictionaries; Genetics -- Dictionary -- English; SCIENCE -- Life Sciences -- Genetics & Genomics; Genetics; Genetik -- lexikon; Dictionary; dictionaries; Dictionaries; Dictionaries; Dictionnaires